Cultural feminism versus post-structuralism: The identity crisis in feminist theory - Alcoff, Linda (Signs, 1988)
Keywords: 1900-1999; 1980-1989; amériques; approches et analyses; cours; cycles supérieurs; discipline; fem1000; fem9000; femmes*; identité sexuelle; philosophie; post-structuralisme; premier cycle; périodes historiques; ressource en ligne; régions géographiques; sciences humaines; sexisme; systèmes d'oppressions; états-unis; études culturelles

White privilege and male privilege: A personal account of coming to see correspondences through work in women's studies - McIntosh, Peggy (Wellesley College, Center for Research on Women, 1988)
Through work to bring materials and perspectives from Women's Studies into the rest of the curriculum, I have often noticed men's unwillingness to grant that they are overprivileged in the curriculum, even though they may grant that women are disadvantaged. Denials that amount to taboos surround the subject of advantages that men gain from women's disadvantages. These denials protect male privilege from being fully recognized, acknowledged, lessened, or ended.
Keywords: 1900-1999; 1980-1989; amériques; approches et analyses; discours dominant; intersectionnalité; privilèges; périodes historiques; racisme; ressource en ligne; régions géographiques; savoir expérientiel; sexisme; systèmes d'oppressions; états-unis